Diagnostic and Therapeutic Value of Hsa_circ_0002594 for T Helper 2-Mediated Allergic Asthma - Huang, Zhenli; Fu, Bohua; Qi, Xuefei; Xu, Yuzhu; Mou, Yong; Zhou, Min; Cao, Yong; Wu, Guorao; Xie, Jungang; Zhao, Jianping; Wang, Yi; Xiong, Weining (International archives of allergy and immunology, 2021)
Circular RNAs (circRNAs) are an endogenous mircoRNA sponge that could act as potential biomarkers for the diagnosis and treatment of diseases. However, the role of circRNAs in asthma is far from clear. The aim of this study is to assess the diagnostic and therapeutic value of hsa_circ_0002594 for T helper (Th) 2-mediated allergic asthma. The expression profiles of hsa_circ_0002594 in CD4+ T cells were revealed by circRNA microarray. Hsa_circ_0002594 expression was confirmed via quantitative real-time PCR (qRT-PCR) in asthmatic patients and healthy subjects. Hsa_circ_0002594 levels were compared between subgroups. The clinical diagnostic abilities and therapeutic response of hsa_circ_0002594 were evaluated. The analyses utilized included a student's t test, nonparametric tests, Spearman's rank-order correlation, Fisher's exact test, and the generation of receiver operating characteristic (ROC) curves. Hsa_circ_0002594 was upregulated and positively correlated with fraction of exhaled nitric oxide while negatively correlated with methacholine dose producing a decrease of 20% from baseline in forced expiratory volume in the first second (PD20) in CD4+ T cells of asthma. Furthermore, hsa_circ_0002594 expression was higher in subgroups with a family history, skin pricking test (SPT)-positive, or Th2-high. The hsa_circ_0002594-high subgroup was more frequently associated with Th2-high biomarker profiles and positive SPT. Hsa_circ_0002594 was decreased after inhaled corticosteroids (ICS) treatment. ROC curve analyses of hsa_circ_0002594 showed high area under the curve values in the presence of ICS or not. Our data suggested that hsa_circ_0002594 was upregulated in CD4+ T cells and might have potential value in the diagnosis and treatment of Th2-mediated allergic asthma.